Neoadjuvant chemotherapy followed by interval debulking surgery versus primary debulking surgery in the advanced epithelial ovarian cancer – a retrospective cohort study - Maričić, Slobodan; Mandić, Aljoša; Dejanović, Ninoslav; Kladar, Nebojša; Popović, Marina; Ivković Kapicl, Tatjana; Gutić, Bojana; Kokanov, Dunja (Vojnosanitetski pregled, 2021)
Background/Aim. The gold standard in treating the advanced ovarian cancer (AOC) is primary debulking surgery (PDS) followed by platinum-based adjuvant chemotherapy. In the AOC, the extent of tumor resection (residual tumor volume) is the most important prognostic factor for overall survival (OS) and progression-free survival (PFS). Neoadjuvant chemotherapy (NACT) followed by interval debulking surgery (IDS) is an experimental treatment of the AOC, introduced in clinical practice in order to improve cytoreduction rate and prolong survival. The aim of this study was to compare the survival and cytoreduction rate of NACT+IDS and PDS in patients with the AOC. Methods. This retrospective cohort study included patients with the AOC, separated into two groups. The first group treated with PDS had 59 patients, while the second group, treated with NACT + IDS, had 33 patients. Results. A lower rate of suboptimal cytoreduction (39.39%) was found in the NACT + IDS group than in the PDS group (57.63%). The percentage of complete cytoreduction was higher in patients treated with NACT + IDS (51.52%) than in those treated with PDS (38.98%). Nevertheless, median OS and PFS were not significantly different between the groups (p < 0.05). OS was 35 months and 31 months in the PDS and NACT + IDS groups, respectively. PFS was 16 months in the PDS and 19 months in the NACT + IDS group. Conclusion. Despite the higher rate of optimal debulking surgery after NACT+ IDS, survival of patients treated with method was not better than those treated with PDS. The decision for either NACT+IDS or PDS should be tailored to the individual patient.